Cardiac morphology in relation to amoebic gill disease history in Atlantic salmon, Salmo salar L - Powell, MD; Barbara Nowak; Mark Adams (2002)
Fish from cages with histories of heavy and light amoebic gill disease (AGD) outbreaks were harvested and the morphology, histology and activities of lactate dehydrogenase determined. Although fish with a history of heavy AGD were smaller, their heart somatic indices were similar to those of fish with a history of light AGD. However, morphometrically the ratios of ventricle axis length and width and axis length and height were significantly higher, and there was an overall thickening of the muscularis compactum in the ventricle of fish with heavy AGD history. There was no difference in the lactate dehydrogenase activity of the ventricle muscle in the two fish groups. These results suggest that the change in ventricle shape associated with AGD was a possible compensation for an increased afterload where the lengthening of the ventricle was compensated for by an increase in muscle thickness, but without any overall ventricular hypertrophy or gain in ventricular mass. This suggests that AGD may be associated with cardiovascular compromise in affected fish.